2019
DOI: 10.1111/jam.14431
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the serovar and antimicrobial resistance in clinical isolates of Salmonella enterica from cattle and pigs between 2002 and 2016 in Japan

Abstract: Aims Given the significance of Salmonella enterica in both human and animal health, and a recent global dissemination of Salmonella 4,[5],12:i:‐, changes in the prevalent serovars and antimicrobial resistance in clinical isolates of Salmonella from cattle and pigs were investigated in Japan. Methods and Results The serovars and antimicrobial susceptibilities of 1605 Salmonella enterica isolated from cattle (n = 894) and swine (n = 711) between 2002 and 2016 were examined. The most common serovar among all samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
(21 reference statements)
2
9
0
Order By: Relevance
“…Despite a number of studies regarding the prevalence and dissemination of cephalosporin resistance in Salmonella from adults and animals, limited information concerning cephalosporin resistance for infections of children is available (Chao et al, 2017;Ma et al, 2018;Feng et al, 2019;Kijima et al, 2019). In our study, we collected Salmonella Enteritidis isolates from children younger than 5 years in China to identify their cephalosporin resistance levels and to determine the transferability of bla CTX-M .…”
Section: Introductionmentioning
confidence: 99%
“…Despite a number of studies regarding the prevalence and dissemination of cephalosporin resistance in Salmonella from adults and animals, limited information concerning cephalosporin resistance for infections of children is available (Chao et al, 2017;Ma et al, 2018;Feng et al, 2019;Kijima et al, 2019). In our study, we collected Salmonella Enteritidis isolates from children younger than 5 years in China to identify their cephalosporin resistance levels and to determine the transferability of bla CTX-M .…”
Section: Introductionmentioning
confidence: 99%
“…Dublin was detected from wildlife in the vicinity of S. Dublin epidemics in cattle as in this study, which implied that S. Dublin seemed to be transmitted from cattle to wildlife (Glawischnig et al, 2017;Jones & Twigg, 1976). A monophasic variant of S. Typhimurium, S. 4,[5],12:i:-, has been increasingly reported as the causative agent of salmonellosis in livestock and humans around the world, including Japan (EFSA, 2018;Kijima et al, 2019;Soyer et al, 2009). Previous studies suggested that a certain epidemic clone was dominant in recent S. 4,[5],12:i:-isolates in Europe and Japan (Arai et al, 2018;Petrovska et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
“…The genetically similar S. Typhimurium strains were shared between wildlife and cattle, but not detected in the same year. S. Typhimurium is a common serotype in both wildlife and cattle (Kijima et al, 2019Simpson et al, 2018Tizard, 2004). Considering the year of detection of isolates in each species for clade IDs 3 and 5, to which both wildlife and cattle isolates belong (Figure 7), cattle strains were possibly transmitted to wildlife and then maintained in the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typhimurium, its monophasic variant, and S . Newport are prevalent in local cattle and pigs [ 15 ], beef and pork may represent sources of Salmonella infections among food workers.…”
Section: Discussionmentioning
confidence: 99%